Status and Prospect of Thermal Analysis of Train Brake Discs - Yuecheng NIU; Fu LI; Xinrong LI; Jincheng LI (机车电传动)
Disc brake is widely used for railway vehicles and cars. During the braking process, the brake disc and the brake shoe generate a large amount of heat, which affects the braking performance, so it is necessary to perform thermal analysis on the brake disc. Based on the application and importance of disc braking on trains, the common materials, structure types and related thermal analysis of train brake discs were introduced, and different thermal analysis methods of brake discs were compared. Finally, the present situation and development direction of thermal analysis of train brake discs were summarized and prospected.